The Vulnerable fishing cat Prionailurus viverrinus and other globally threatened species in Cambodia's coastal mangroves. Issue 4 (27th November 2017) - Thaung, Ret; Herranz Muñoz, Vanessa; Holden, Jeremy; Willcox, Daniel; Souter, Nicholas J.
Abstract: The Vulnerable fishing cat Prionailurus viverrinus faces a perilous future in South-east Asia. It was last sighted in Cambodia in 2003. We deployed 16 camera traps at four sites in southern Cambodia during January–May 2015 to determine if the fishing cat was still present in the country. Eight photograph/video captures of fishing cats were recorded from the mangroves in Peam Krasop Wildlife Sanctuary and one from Ream National Park, but there were no records from Botum Sakor National Park or Prey Nup. A number of other globally threatened species were also photographed in Peam Krasop Wildlife Sanctuary: the Sunda pangolin Manis javanica, the hog deer Axis porcinus and the large-spotted civet Viverra megaspila . We learnt of the killing of an alleged fishing cat at the Sanctuary in July 2015 in retaliation for raiding fishing nets. Illegal hunting and capture of fishing cats for the wildlife trade were reported by local informants at all sites. We provide photographic and video evidence of the fishing cats and highlight the importance of Cambodia's mangroves for threatened species conservation.